Situation Report: Hungary, 31 March 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. National Assembly Prepares to Enact Major Political Reforms / by Edith Markos Will the Celebration of the National Holiday Lead to Political Divisiveness / by Judith Pataki March 15 Demonstrations Symbolize Turning Point in Hungary / by Edith Markos Democratic Forum Holds First National Congress / by Alfred Reisch Economic Developments in 1988 / by Karoly Okolicsanyi Current Problems of Hungarian Agriculture / by Karoly Okolicsanyi Hungary's Intra-CMEA Trade Diminishes amid Troubled Relations / by Karoly Okolicsanyi